THE ROLE OF LEADERSHIP, WORK CULTURE, AND TRAINING ON EMPLOYEE PERFORMANCE: A QUALITATIVE STUDY OF SUMATERA'S NASI LAUK UMKM - Amru Usman; Rusydi Abubakar; Khairil Anwar (RADJA PUBLIKA, 2025)
This study aims to examine the influence of leadership, work culture, and training on employee performance at the culinary MSME